Association between hypoglycemia risk and hemoglobin A1C in patients with type 2 diabetes mellitus. (2nd August 2016) - Yu, Shengsheng; Fu, Alex Z.; Engel, Samuel S.; Shankar, R. Ravi; Radican, Larry
Abstract: Objective: To better manage type 2 diabetes mellitus (T2DM), the tradeoff between improved glycemic control and hypoglycemia should be evaluated. The purpose of this study was to assess the relationship between hypoglycemia and hemoglobin A1c (HbA1c) in a real-world population. Research design and methods: Real-Life Effectiveness and Care Patterns of Diabetes Management (RECAP-DM) was a multi-center, observational study. Patients ≥30 years old using any oral anti-hyperglycemic agent were recruited from seven European and five Asian countries between 2006 and 2007. Hypoglycemia events were collected through patient-reported questionnaires. HbA1c data was collected through chart review. Logistic regression was performed to assess the relationship between hypoglycemia and the most proximate HbA1c levels adjusting for potential confounders (demographics, clinical variables, other medication use, and comorbid conditions). Results: A total of 4399 patients were recruited and analyzed. Mean age was 60 years, 52% were male, and 75% were on sulfonylureas (S.U.s). Respectively, 37% or 42% of patients reported hypoglycemia in the past 6 (Asia) or 12 months (Europe) before recruitment. Prevalence of hypoglycemia increased significantly (33% to 40%) as HbA1c decreased ( p = 0.035). The same trend was also observed among S.U.-treated patients ( p < 0.01). After adjusting for confounders, hypoglycemia prevalence was significantly higher for HbA1c <7.0% (odds ratio [O.R.] = 1.66 [95% C.I. 1.21, 2.28]; p = 0.002) vs. HbA1c ≥10.0%. Limitations: Our analyses pooled data from Asia and Europe, which differed in terms of the recall period for ascertaining hypoglycemia symptoms and the timing of latest HbA1c measure. Conclusions: Lower HbA1c level was associated with higher hypoglycemia prevalence among S.U.-treated patients. HbA1c level should be taken into consideration when reporting hypoglycemia prevalence.